Preditores da necessidade de oxigenoterapia, de suporte ventilatório e do óbito em adultos hospitalizados por Covid - Diniz, Dimas Gabriel Sales (2023)
Background: covid-19 had a major impact on public health worldwide, as due to the high transmissibility of the virus and globalization, the disease became a pandemic within 90 days of the first recorded case. Vaccines now exist, but with the unequal distribution of this resource around the world, there is a serious risk of the emergence of viral strains with high immune escape. Therefore, it is necessary to understand the factors that cause the aggravation of the disease in order to improve the management of covid-19 acute respiratory distress syndrome. Objective: identify predictors of oxygen requirement, ventilatory support, and death in patients hospitalized for covid-19 acute respiratory distress syndrome. Methods: retrospective cohort study with secondary data from medical records of 330 patients admitted in 2020 for covid-19. The data were collected from August 2022 to January 2023, being divided into subgroups by age group, gender, origin, time to hospital admission, length of stay, laboratory tests, ionogram, fluid balance, comorbidities and outcome, then analyzed by the statistical program SPSS 22.0 with 95% significance. Results: age groups 51 to 65 years (LF: p= 0.044, OR= 3.41) and 66 to 80 years (LF: p= 0.001, OR= 13.25; HF: p= 0.030, OR= 4.14), the time to hospital admission from 6 to 10 days (LF: p= 0.022, OR= 2.74), altered c-reactive protein (LF: p= 0.039, OR= 2.56; HF: p= 0.028, OR= 2.96) and diabetes (HF: p= 0.022, OR= 2.02) were more likely to need oxygen therapy than others. For ventilatory support, those with altered c-reactive protein (NIMV: p= 0.021, OR= 5.62), smokers (NIMV: p= 0.009, OR= 2.20), aged 66 to 80 years (IMV: p= 0.010, OR= 6.15), positive fluid balance (IMV: p= 0.017, OR= 2.68) and altered creatinine (IMV: p= 0.001, OR= 2.57) were more likely to require it than others. Finally, age group between 66 and 80 years (p= 0.038, OR= 9.72), positive fluid balance (p= 0.002, OR= 4.02) and altered creatinine (p= 0.026, OR= 2.07) exhibited higher chances of death than the others. Conclusion: factors that most influenced the use of oxygen therapy, ventilatory support and death were those related to age (66 to 80 years), inflammation (c-reactive protein) and renal function (fluid balance and creatinine).